2023
DOI: 10.1167/iovs.64.1.16
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Scleral Thickness and Choroidal Structure in Central Serous Chorioretinopathy

Abstract: Purpose Central serous chorioretinopathy (CSC) is a retinal disorder characterized by serous retinal detachment with or without pigment epithelial detachment in the posterior pole of the eye. We aimed to elucidate the relationship between scleral thickness and choroidal structure in CSC eyes. Methods This single-center retrospective study included 111 eyes of 111 CSC patients. Using swept-source optical coherence tomography, the horizontal cross-sectional images of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 47 publications
1
3
0
Order By: Relevance
“…This is because we found a large variation in rectus muscle attachment sites, with some anterior to 6 mm and others posterior to 6 mm. However, our method revealed that AST in CSCR eyes was higher than normal control eyes, replicating results of previous studies [ 7 , 16 , 17 ]. Third, AST has limited correlation with scleral thickness around the vortex vein, which is relevant in terms of the venous overload hypothesis.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This is because we found a large variation in rectus muscle attachment sites, with some anterior to 6 mm and others posterior to 6 mm. However, our method revealed that AST in CSCR eyes was higher than normal control eyes, replicating results of previous studies [ 7 , 16 , 17 ]. Third, AST has limited correlation with scleral thickness around the vortex vein, which is relevant in terms of the venous overload hypothesis.…”
Section: Discussionsupporting
confidence: 91%
“…Anteriorly, the sclera was distinguished from the hyporeflective rectus muscles; posteriorly, the sclera was distinguished from the choroid appearing as a hyporeflective band. Previous studies [ 7 , 16 , 17 ] have used a constant distance from the scleral spur as the measurement point for AST. However, due to the variability in muscle attachment sites and the abrupt change in scleral thickness at these sites, we adjusted our measurement locations.…”
Section: Methodsmentioning
confidence: 99%
“…As the cause of this regional difference is not clear from the present cross sectional study, future prospective studies on the development of VVA in childhood are needed. In addition, scleral thickness was not associated with the running patterns of Haller's vessels and was positively correlated with choroidal thickness, 27 , 37 whereas the malposition of the VVA was associated with the running patterns of Haller's vessels and not with choroidal thickness. Thus, the sclera and the VVA may have different relationships with the choroid.…”
Section: Discussionmentioning
confidence: 76%
“…It excels in demarcating the boundaries of anterior segment structures compared to SD-OCT (20). A few recent studies successfully measured scleral thickness in different study groups with the help of SS-OCT (21)(22)(23). However, to our knowledge, no study has yet assessed scleral thickness in SLE patients utilizing SS-OCT.…”
Section: Introductionmentioning
confidence: 99%